KESULTANAN TERNATE PADA MASA PENDUDUKAN JEPANG (1942-1945) - Hasim, Rustam (JURNAL ILMU BUDAYA, 2023)
This paper discusses the role of the sultan of Ternate Iskandar Djabir Sjah during the Japanese occupation of North Maluku. Basically, this study is historical research on political activities involving the Sultanate elite using historical methods ranging from heuristics to historiography. The sources used in this study consisted of written sources and interviews. This study concludes that since the presence of Japan in North Maluku in 1942, they wanted to conquer the Sultanate of Ternate under their control. Political activity is prohibited and restricted, socio-economic life is in decline. The population is regulated in such a way that it is easy to supervise. All economic activity is aimed at helping the armed forces. In the field of education, schools are still operating normally, but their function is as a place for Japanese propaganda.